The Relationship Between Acetylcholinesterase, Neurotransmitter Levels, Calcium, Vitamin D3, and Trace Minerals in Autism Spectrum Disorder - Ako Saber Kaky; Sayran Sattar Saleh (Baghdad Journal of Biochemistry and Applied Biological Sciences)
This study aimed to investigate the potential associations between acetylcholinesterase (AChE) activity, neurotransmitters, trace minerals, and autism spectrum disorder (ASD). A comparative analysis was conducted between 96 ASD patients and 96 healthy controls. Results revealed significantly lower AChE activity and specific activity in ASD patients compared to controls, corroborating previous findings linking AChE with neurological disorders. Furthermore, GABA and GRIA1 levels were elevated in ASD patients, while oxytocin and HDAC-2 were decreased. Notably, calcium and vitamin D levels were significantly lower in the ASD group, while magnesium and zinc levels were increased. Copper levels showed a decrease in ASD patients. Correlation analysis indicated significant negative correlations between AChE activity and oxytocin, and positive correlations between AChE activity and vitamin D, GABA, and zinc. These findings suggest potential dysregulations in the cholinergic, GABAergic, glutamatergic, and oxytocinergic systems, as well as imbalances in trace minerals, which may contribute to the pathophysiology of ASD. Further research is warranted to elucidate the underlying mechanisms and explore potential therapeutic interventions targeting these biochemical markers